INTENSITY MODULATED RADIOTHERAPY IN POSTOPERATIVE TREATMENT OF CERVICAL CANCER - Marjanović, Dragoslava; Plešinac Karapandžić, Vesna (Medicinski podmladak, 2019)
Introduction: Postoperative radiotherapy in patients with cervical cancer significantly reduces the risk of loco-regional disease relapse, but at the same time is associated with increased toxicity at surrounding healthy organs and tissues. The occurrence of toxicity can significantly reduce the patient’s quality of life, despite the complete remission of the disease. Aim: In this review article, we present modern radiotherapy technique - intensity modulated radiotherapy (IMRT), its advantages and disadvantages. Significant number of studies documented the results of postoperative IMRT role in treatment of cervical cancer, in reducing acute and late toxicity. Conclusions: Compared to previously used modalities of irradiation, IMRT is a complex radiotherapy technique - technically and time-consuming - which achieves escalation of the dose in the target volume, with better organ risk management, while decrease the frequency of acute and chronic complications and improve the quality of life after treatment. Of particular importance is the IMRT in postoperative approach in patients with a good prognosis Keywords: cervical cancer, toxicity, intensity modulated radiotherapy